High Concentrations of Tilmicosin Promote the Spread of Multidrug Resistance Gene tolC in the Pig Gut Microbiome Through Mobile Genetic Elements - Tao Chen; Minxing Zhao; Majian Chen; Xiaoyue Tang; Yuliang Qian; Xiaoting Li; Yan Wang; Xindi Liao; Yinbao Wu (Animals)
The impact of antibiotic therapy on the spread of antibiotic resistance genes (ARGs) and its relationship to gut microbiota remains unclear. This study investigated changes in ARGs, mobile genetic elements (MGEs), and gut microbial composition following tilmicosin administration in pigs. Thirty pigs were randomly divided into control (CK), low-concentration (0.2 g/kg; L), and high-concentration (0.4 g/kg; H) groups. Tilmicosin concentration in manure peaked on day 16 of dosing and dropped below detectable levels by day 13 of the withdrawal period. While tilmicosin did not significantly affect the total abundance of macrolide resistance genes (MRGs) (p > 0.05), it significantly increased the abundance of the multidrug resistance gene tolC in the H group compared with the L and CK groups during the withdrawal period (p < 0.05). This increase was associated with a coincidental rise in the abundance of MGEs (e.g., int1 and int2) and the growth of potential tolC-hosting bacteria such as Paenalcaligenes and Proteiniclasticum. Redundancy analysis showed gut microbial composition as the primary driver of MRG abundance, with MGEs, tilmicosin concentration, and manure physicochemical properties playing secondary roles. These findings suggest that high-dose tilmicosin may alter the gut microbiota and promote ARG spread via MGE-mediated transfer.